INNOVATIONS IN MACRO AND MICROECONOMICS - Ikromova Kamola (Web of Journals Publishing, 2024)
This article explores contemporary innovations in macro and microeconomics, focusing on technological, theoretical, and practical advancements. The paper examines significant contributions from recent literature, highlights innovative methodologies, and discusses the implications of these innovations for policy-making and business strategies.
Keywords: Economics, Macroinnovation, microinnovation, economic policy, behavioral economics, big data, digital economy.